Skin γδ T Cells and Their Function in Wound Healing - Hu, Wengang; Shang, Ruoyu; Yang, Jiacai; Chen, Cheng; Liu, Zhihui; Liang, Guangping; He, Weifeng; Luo, Gaoxing (Frontiers in Immunology, 2022)
For the skin immune system, γδ T cells are important components, which help in defensing against damage and infection of skin. Compared to the conventional αβ T cells, γδ T cells have their own differentiation, development and activation characteristics. In adult mice, dendritic epidermal T cells (DETCs), Vγ4 and Vγ6 γδ T cells are the main subsets of skin, the coordination and interaction among them play a crucial role in wound repair. To get a clear overview of γδ T cells, this review synopsizes their derivation, development, colonization and activation, and focuses their function in acute and chronic wound healing, as well as the underlining mechanism. The aim of this paper is to provide cues for the study of human epidermal γδ T cells and the potential treatment for skin rehabilitation.